Estimation of stature from radiographic measurement of foot dimensions: Truncated foot length may be more reliable than full foot length - Gwani, Abdullahi Suleiman; Salihu, Abubakar Tijjani; Garba, Isa Sa'idu; Rufa'i, Adamu Ahmad (Journal of forensic and legal medicine, 2017)
Foot length has been shown to be a reliable dimension for estimation of stature. However, phalanges of the foot are very small bones and their length may not be proportional to person's stature. Thus, we hypothesized that foot length measured excluding the phalanges, the truncated foot length, may be more reliable in stature estimation than full foot length. This study, therefore, aimed at comparing the accuracy of the regression equations derived from the truncated foot length and the full foot length. The study recruited a sample of 32 young adults (16 males and 16 females) aged from 20 to 35 years. Lateral radiographs of the right feet were obtained for each subject in a bilateral standing position while maintaining equal weight on both feet. Standing height of the participants was measured with a stadiometer. Truncated foot length and full foot length were measured on the lateral radiographs of the foot. Independent t-test was used to check for mean differences in the dimensions between genders. Linear regression analysis was used to determine the equations for stature estimation. Intra and inter-observer reliability were calculated from four precision estimates: absolute technical error of measurement (aTEM), relative technical error of measurement (rTEM), coefficient of reliability (Rr) and coefficient of variation (Cv). All the dimensions measured were significantly larger in males than females. Linear regression equations were derived for estimation of stature using both the truncated foot length and full foot length. The regression equations derived from truncated foot length have larger correlation coefficient, coefficient of determination, adjusted coefficient of determination as well as smaller standard error of estimation than those derived from full foot length. All the precision estimates showed that the measurement errors are within acceptable limits. This study suggests that even if the full foot length is available, excluding the phalanges may give more accurate stature estimation. •Males have significantly larger dimensions than females.•Truncated foot length may give more accurate stature estimation than full foot length.•Truncated foot length offers another alternative for stature estimation from foot dimensions in case of toe deformities.